The Oxford Handbook of Group and Organizational Learning 2019
DOI: 10.1093/oxfordhb/9780190263362.013.7
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Learning and Multiteam Systems

Abstract: Multiteam systems consist of two or more teams, each of which pursues subordinate team goals, while working interdependently with at least one other team toward a superordinate goal. Many teams work in these larger organizational systems, where oft-cited challenges involve learning processes within and between teams. This chapter brings a learning perspective to multiteam systems and a multiteam system perspective to organizational learning. Several classic illustrations of organizational learning—for example,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…More observational research is needed to better understand what a transformational learning process "looks like" in MTSs. In terms of flow, we found that in some cases, the MTS engaged in learning processes as a whole, in some cases, processes started in the leadership team (Davison et al, 2012) or in a component team (Crossan et al, 1999;DeChurch et al, 2020) and then flowed into the rest of the MTS. We did not see evidence in these cases of learning flow via multi-team memberships (O'Leary et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…More observational research is needed to better understand what a transformational learning process "looks like" in MTSs. In terms of flow, we found that in some cases, the MTS engaged in learning processes as a whole, in some cases, processes started in the leadership team (Davison et al, 2012) or in a component team (Crossan et al, 1999;DeChurch et al, 2020) and then flowed into the rest of the MTS. We did not see evidence in these cases of learning flow via multi-team memberships (O'Leary et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Second, learning can happen in the MTS's leadership team (Davison et al, 2012), and the learning can flow down to the component teams via the leaders or integrating members (team members who communicate with members of the other teams). Third, learning can happen first in a component team and flow into the MTS as a whole (Crossan et al, 1999;DeChurch et al, 2020). Fourth, learning can flow horizontally from team to team via multi-team memberships (O'Leary et al, 2011).…”
Section: Types Of Learning Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…Mental models develop over time through experiences, interactions with others, and vicarious learning [19]. A lack of shared mental models among multiteam system members hampers their ability to collaborate and coordinate their efforts [14,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%